Clinical utility of antinuclear antibody tests in children - Kickingbird Lauren M; McGhee Julie L; Jarvis James N (BMC, 2004)
Abstract Background Antinuclear antibody (ANA) tests are frequently used to screen children for chronic inflammatory diseases such as systemic lupus erythematosus (SLE). However, the diagnostic utility of this test is limited because of the large number of healthy children who have low-titer positive tests. We sought to determine the clinical utility of ANA tests in screening children for rheumatic disease and to determine whether there are specific signs or symptoms that enhance the clinical utility of ANA tests in children. Methods We undertook a retrospective analysis of 509 new patient referrals. Charts of patients referred because of results of ANA testing were selected for further analysis. Children with JRA, SLE, and other conditions were compared using demographic data, chief complaints at the time of presentation, and ANA titers. Results One hundred ten patients were referred because of an ANA test interpreted as positive. Ten patients were subsequently diagnosed with SLE. In addition, we identified one patient with mixed connective tissue disease, and an additional child with idiopathic Raynaud's phenomenon. Eighteen children of the children referred for a positive ANA test had juvenile rheumatoid arthritis (JRA). Another 80 children with positive ANA tests were identified, the majority of whom (n = 39, 49%) had musculoskeletal pain syndromes. Neither the presence nor the titer of ANA served to distinguish children with JRA from children with other musculoskeletal conditions. Children with JRA were readily identified on the basis of the history and physical examination. Children with SLE were therefore compared with children with positive ANA tests who did not have JRA, designated the "comparison group." Non-urticarial rash was more common in children with SLE than in children without chronic inflammatory disease (p = 0.007). Children with SLE were also older (mean ± sd = 14.2 ± 2.5 years) than the comparison group (11.0 ± 3.6 years; p = 0.001). ANA titer was also a significant discriminator between children with SLE and children without chronic inflammatory disease. The median ANA titer in children with SLE was 1: 1,080 compared with 1:160 for other children (p < 0.0001). ANA titers of ≥1,080 had a positive predictive value for SLE of 1.0 while titers of ≤1: 360 had a negative predictive value for lupus of 0.84. Conclusion Age and ANA titer assist in discriminating children with SLE from children with other conditions. ANA tests are of no diagnostic utility in either making or excluding the diagnosis of JRA.